2018
DOI: 10.16986/huje.2018041735
|View full text |Cite
|
Sign up to set email alerts
|

Eğitimcilerin Örgütsel Sessizliklerinde Cinsiyetin ve Medenî Durumun Etkisi: Bir Meta Analiz Çalışması

Abstract: ÖZ:Bir meta-analiz çalışması olan bu araştırmada, eğitim çalışanlarının örgütsel sessizliğinde cinsiyet ve medenî durumun etkisi incelenmiştir. Araştırmada, örgütsel sessizlik ile cinsiyet arasındaki ilişkilerin incelendiği birbirinden bağımsız 20 araştırma bir araya getirilerek 7514 kişilik örneklem grubu; örgütsel sessizlikle medenî durum arasındaki ilişkilerin incelendiği birbirinden bağımsız 9 araştırma bir araya getirilerek 2919 kişilik örneklem grubu elde edilmiştir. Araştırmada, rastgele etki modeline g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…No statistically significant difference was found for the gender variable. According to the results of the research, female teachers and male teachers exhibit similar silence behaviors.While this result of the study is similar to some research results Ünlü, Hamedoğlu and Yaman, 2015;Dal, 2017;Önder, 2017;Demir and Cömert, 2018), it also differs with some research results (Brisfield, 2009;Çakıcı , 2010;Kahveci and Demirtaş, 2013;Tülibaş and Celep, 2014;Çiçek-Sağlam and Yüksel, 2015;Demirtaş and Nacar, 2018;Tulunay and Önder, 2019 ). In studies that differed from the results of the research, it was found that female teachers were more silent than male teachers.The reasons for this situation can be explained as the gender perspective and the fact that the majority of the managers are male.…”
Section: Results Of Teachers' Perceptions Of Organizational Silence O...supporting
confidence: 87%
See 1 more Smart Citation
“…No statistically significant difference was found for the gender variable. According to the results of the research, female teachers and male teachers exhibit similar silence behaviors.While this result of the study is similar to some research results Ünlü, Hamedoğlu and Yaman, 2015;Dal, 2017;Önder, 2017;Demir and Cömert, 2018), it also differs with some research results (Brisfield, 2009;Çakıcı , 2010;Kahveci and Demirtaş, 2013;Tülibaş and Celep, 2014;Çiçek-Sağlam and Yüksel, 2015;Demirtaş and Nacar, 2018;Tulunay and Önder, 2019 ). In studies that differed from the results of the research, it was found that female teachers were more silent than male teachers.The reasons for this situation can be explained as the gender perspective and the fact that the majority of the managers are male.…”
Section: Results Of Teachers' Perceptions Of Organizational Silence O...supporting
confidence: 87%
“…As a result of the research, it was concluded that the organizational silence perceptions of the teachers did not show a statistically significant difference according to the marital status variable. In other words, it was concluded that teachers' being married or single does not make any difference on silence.This result of the research is similar to the results of different studies on organizational silence (Özdemir, 2015;Sevgin, 2015;Aydın, 2016;Aktaş 2019;Gülenç, 2019;Varol, 2021).Unlike these studies, according to the meta-analysis study conducted by TulunayAteş and Önder (2019), it was concluded that marital status had a weak effect on organizational silence.In some studies, it has been found that married teachers are more silent than single teachers (Tulunay and Önder, 2019). In that regard, it can be argued that the fact that married teachers have more responsibilities than single teachers has an effect on their silence.…”
Section: Results Of Teachers' Perceptions Of Organizational Silence O...mentioning
confidence: 99%